2018
DOI: 10.5897/ajmr2018.8864
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the extracts of Albizia masikororum R.Vig., a Fabaceae from Madagascar

Abstract: This study is aimed at the assessment of antimicrobial potential of Albizia masikororum, a Malagasy Fabaceae. Hexanic and methanolic extracts from fruit pods, stem bark, leaves and seeds were tested by disc diffusion and microdilution methods on 10 pathogenic microorganisms including four Gram positive bacteria, five Gram negative bacteria and one yeast. Only the leaf and seed methanolic extracts, LME and SME respectively, were active on some bacteria. LME and SME had a broad-spectrum activity, with SME more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies showed that the antibacterial activity of plant's extracts depends mainly on their richness on polyphenol contents [351]. Anjarasoa et al [352] reported that the antimicrobial activity of Albizia masikororum extract (fabaceae) may be due to the richness of the extract with different chemical groups known for their antimicrobial properties like saponins and phenolic compounds. The antimicrobial activity of A. indica extract observed in the present work against S. aureus strain was higher than the activity found in the study of Mistry et al [353], where A. indica extract presented an inhibition zone of 14.33 mm against S. aureus strain.…”
Section: Determination Of the Antibacterial Activity Of Anthyllis Vul...mentioning
confidence: 99%
“…Previous studies showed that the antibacterial activity of plant's extracts depends mainly on their richness on polyphenol contents [351]. Anjarasoa et al [352] reported that the antimicrobial activity of Albizia masikororum extract (fabaceae) may be due to the richness of the extract with different chemical groups known for their antimicrobial properties like saponins and phenolic compounds. The antimicrobial activity of A. indica extract observed in the present work against S. aureus strain was higher than the activity found in the study of Mistry et al [353], where A. indica extract presented an inhibition zone of 14.33 mm against S. aureus strain.…”
Section: Determination Of the Antibacterial Activity Of Anthyllis Vul...mentioning
confidence: 99%